أثر الفكر الديني في المجتمع الرافديني - رشيد, عادل فائق (Al-Adab Journal, 2019)
Religious ideology have had a major effect upon ancient Mesopotamian societies , despite the oldest writing attempts which date back to the mid of the fourth Millennium B.C were its tablets mentioned the oldest Gods, But we found out that the earliest testimonials of religion effect date back to those early agricultural families that practiced farming and domesticated animals, ose early agricultural families that practiced farming and domesticated animals, testimonials of religion effect date back to t within the Neolithic period 6750 B.C, besides, religious ideology was the main factor behind establishing and creating laws and that almost none of the known Codes lacks the mention of Gods and that they "Gods" were attributed for legislating the laws.The Study is divided on number of axis, the first is centered around the idea of ground fertility and the role of the so called (Mother Goddess) in increasing the amount of crops, the second axis come to confirm the role of Gods in creating laws, The Third enhanced the idea of the temple being the city's spiritual center and its effect in establishing cities, forth axis is devoted for the theory of divine kingship and that it is Gods who decide who represents it on earth, fifth axis dealt with Sacred Marriage or so known in Latin (Hieros Gamos) for the continuity of Spring, sixth axis debated burying practice , the after death creed and the Gods of the underworld, The final axis debates the occurrence of polytheists and its interpretations of natural phenomenon worshipping.